Efikasi diri dalam pengasuhan ditinjau dari struktur keluarga - Pratiwi, Pradipta Christy; Yustitia, Hani (Konsorsium Psikologi Ilmiah Nusantara, 2024)
Parents require parenting self-efficacy to optimally perform parental tasks and responsibilities. Family structure is a powerful predictor of self-efficacy in parenting. This study aims to compare parenting self-efficacy for mothers from nuclear families compared to those from extended families. The sample size was 149 early adult mothers obtained through accidental sampling, of which 88 participants were from nuclear families. Participants completed The Parenting Self-Efficacy Scale. The findings indicate that mothers from nuclear families had significantly stronger parenting self-efficacy than those from extended families. The result highlights that mothers in nuclear families can provide a more comfortable learning environment and therefore enforce consistent parenting standards than mothers in extended families.